A Systematic Review: Optimization of Extracts Psidium Guajava L. By Using Ultrasound-Assisted with Soxhlet Extraction in Application of Food Preservation - Mohd Rozlan, Nur Aqidah; Che Pa, Nasrul Fikry (Progress in Engineering Application and Technology, 2021)
Natural antimicrobial compounds from extracted of medicinal plant has bring a lot of attention to researchers all around the world since synthetic antimicrobial agents can lead to health issues. Natural antimicrobial that was produced from extracted plant has characteristic to inhibits the growth of microorganism in which could lead to several of diseases. Even so, the production of natural antimicrobial agent depend on the employment of extraction technique. In this research, ultrasound-assisted with Soxhlet extraction were conducted on Psidium guajava L. Highest extraction efficiency obtained by using combination of ultrasound-assisted with Soxhlet extraction in which utilised by 95% of ethanol and highest concentration of quercetin produce in fresh leaves were found in this research with (40.96±1.29) and (63.9±8.5), respectively. Therefore, the revised outcome of this systematic analysis give possible value of Psidium guajava L. as an antimicrobial agents which can be applied in food processing. Based on four databases implemented in this research (PubMED, Tandfonline, Google Scholar and Science Direct), the search strategy was built with the search terms (“Psidium guajava L.”, “antimicrobial activity”, “ultrasound-assisted extraction”, and “Soxhlet extraction”). The unified data was analysed using PRISMA rules, and 504 papers were separated after the identical articles were eliminated. 401 papers were eventually excluded when they did not match the inclusion requirements and 103 articles were re-evaluated for eligibility again. Optimum condition for ultrasound-assisted with Soxhlet extraction were evaluated by varying ultrasound-assisted extraction temperature and time and also altering the temperature of Soxhlet extraction. The findings of this research study has shown that the optimum condition of extracts Psidium guajava L. is at 60 °C of sonication temperature and 35 minutes of extraction time. Whereas, the extraction that undergoes in Soxhlet will be at 45 °C. Best solvents between methanol and ethanol which applied in Soxhlet extraction were studied. Thus, according to the research study that has been done, ethanol was chosen as the suitable solvent in extraction of Psidium guajava L. due to high production of total phenolic compound was produce (40.50±0.88). In short, ultrasound-assisted with Soxhlet extraction can enhance the production of antimicrobial activity from extracts of Psidium guajava L.